Assessing Sanitation Perceptions Before and During COVID-19: Implications for Community Welfare - Araune, Paolo (Alta Dharma Publisher, 2024)
Background & Aim: Proper sanitation practices are vital for community welfare, particularly in rural areas with limited access to clean water. This study assessed residents' perceptions of sanitation practices before and during the COVID-19 pandemic. It explored the influence of age, gender, educational attainment, and family size on these perceptions to identify the most significant predictor. Methods & Materials: Conducted in a subdivision community in Northern Mindanao, Philippines, this descriptive quantitative study focused on residents aged 18 to 65 without diagnosed mental disorders. Using simple random sampling and Cochran's formula, 289 respondents represented the population. Statistical analyses, including ANOVA, t-tests, F-tests, and multiple regression, were used to explore relationships between variables and determine significant differences. Results: Significant differences existed in respondents' sanitation perceptions before and during the pandemic. Older individuals had higher perceptions before, while middle-aged individuals showed higher perceptions during the pandemic. Females consistently demonstrated higher perception levels than males. Education influenced perceptions, with college-educated respondents having the highest before and those with elementary education showing the highest during the pandemic. Family size significantly affected perceptions before. Gender emerged as the most predictive variable for sanitation perceptions before and during the pandemic: multiple regression identified age, gender, and family size as significant predictors. Conclusion: A Continued health education effort is crucial for sustaining correct perceptions. Addressing gender disparities and tailoring interventions to diverse age groups are essential for promoting equitable sanitation access and fostering healthier communities. Consistency in health education is vital for sustaining positive perceptions and ensuring behavioral change beyond the pandemic.